2020
DOI: 10.3390/plants9121633
|View full text |Cite
|
Sign up to set email alerts
|

Celery (Apium graveolens L.) Performances as Subjected to Different Sources of Protein Hydrolysates

Abstract: The vegetable production sector is currently fronting several issues mainly connected to the increasing demand of high quality food produced in accordance with sustainable horticultural technologies. The application of biostimulants, particularly protein hydrolysates (PHs), might be favorable to optimize water and mineral uptake and plant utilization and to increase both production performance and quality feature of vegetable crops. The present study was carried out on celery plants grown in a tunnel to apprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
12
31
1
Order By: Relevance
“…One of the most pioneeristic agronomic practices to meet these challenges is the use of plant biostimulants which can elicit growth and development, productivity, abiotic stress tolerance and quality of plants [3,4]. Several authors [5][6][7][8][9][10][11][12] have reported that biostimulants can promote primary and secondary metabolism in vegetables, modulating micro-and macronutrient uptake and assimilation, buildup of phytochemicals and tolerance to abiotic distresses. Among plant biostimulants, seaweed extracts (SEs), especially the brown macro-algae, are often used for their content in signaling molecules such as polysaccharides, betaines, macroand micronutrients and phytohormones which enhance plant performance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most pioneeristic agronomic practices to meet these challenges is the use of plant biostimulants which can elicit growth and development, productivity, abiotic stress tolerance and quality of plants [3,4]. Several authors [5][6][7][8][9][10][11][12] have reported that biostimulants can promote primary and secondary metabolism in vegetables, modulating micro-and macronutrient uptake and assimilation, buildup of phytochemicals and tolerance to abiotic distresses. Among plant biostimulants, seaweed extracts (SEs), especially the brown macro-algae, are often used for their content in signaling molecules such as polysaccharides, betaines, macroand micronutrients and phytohormones which enhance plant performance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables, such as tomato ( Polo and Mata, 2018 ; Sestili et al, 2018 ; Casadesús et al, 2019 ), rocket ( Caruso et al, 2019 ), celery ( Consentino et al, 2020 ), lettuce ( Polo et al, 2006 ; Xu and Mou, 2017 ), basil ( Rouphael et al, 2021 ), and spinach ( Kunicki et al, 2010 ), and tree crops, such as kiwifruit ( Quartieri et al, 2002 ), papaya ( Morales-Pajan and Stall, 2003 ), and passion fruit ( Morales-Pajan and Stall, 2004 ), have been tested with animal-based PHs, with the aim of improving plant performance and abiotic stress resistance. Less attention to the use of animal-based PH biostimulants has been paid for ornamental species, especially bedding plants.…”
Section: Introductionmentioning
confidence: 99%
“…Another category of biostimulants widely used in horticulture is protein hydrolysates and nitrogen-containing compounds. There are several commercial products available derived from plant or animal proteins with various applications in horticultural crops during the last few years [128][129][130]. For example, one of the first studies was conducted on common bean with protein hydrolysates derived from tomato plant residues and reported a significant increase in nitrogen assimilation of bean [131].…”
Section: Practical Applications Of Biostimulants and Biostimulatory Products On Horticultural Cropsmentioning
confidence: 99%